Sexual Abuse of Children with Special Needs: A Literature Review - Rahmawati, Selvi; Marlina, Marlina; Efrina, Elsa; Nasri, Yosa Yulia; Handayani, Endang Sri (Department of Special Education, 2025)
Sexual abuse against children with special needs is a critical issue requiring multidisciplinary attention. Children with special needs are highly vulnerable due to communication barriers, dependence on adults, and limited understanding of risky situations. Abuse includes verbal, physical, psychological, and digital forms. Contributing factors are low societal awareness and inadequate tailored sexual education. Cases often occur in close environments like schools, families, or communities. This study aims to analyze sexual abuse patterns among children with special needs and raise awareness. Using a PRISMA-based Systematic Literature Review (SLR), it examines abuse types, forms, and causes. Data from Scopus (2015–2025) were filtered using keywords like 'sexual abuse' and 'children with special needs, yielding 79 articles for bibliometric analysis. Findings highlight that children with intellectual disabilities (e.g., Down syndrome) face heightened risks of verbal, physical, and digital abuse, exacerbated by gender inequality and lack of inclusive education. The study underscores the need for policy reforms and protective education programs.